Thermo-Hydric Modeling of The Water Retention Curve Based on The Hydric Model of Van Genuchten - Moulay Smaine, Ghembaza; Tewfik, Belal (Aceh International Journal of Science and Technology, 2023)
In this paper, we propose an extension for a model of unsaturated soils developed by Van Genuchten (1980) and obtain a thermos-hydric model to study the influence of temperature on the water retention curve. A brief presentation of the Model is described using the independent parameter modeling method. The proposed hydrometric Model makes it possible to predict, from the experimental measurements carried out on drainage-humidification paths for an ambient temperature, the WRC (water retention curve) at high temperatures while knowing the initial state of the soil studied (Compacted or in the form of a paste). We show in this Model the existence of the hysteresis phenomenon between the drainage and humidification path and the shift of the downward retention curves showing a slight decrease in the water content as the temperature increases. To validate this Model, three experimental results from the literature are simulated. The results obtained by simulating the experimental curves show the ability of the proposed Model to predict WRC at high temperatures. These results considerably reduce the number of experimental trials in geotechnical and geothermal unsaturated soils.